2004
DOI: 10.1111/j.1365-2648.2004.03119.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretations of stillbirth

Abstract: Culturally bound taboos against talking about death, participating in death-related events, and expressing grief in public affect the adaptation and grieving processes of Taiwanese women who have had a stillbirth. Nurses should, therefore, make an effort to listen to the perspectives of such patients in order to assist them with coming to terms with their loss. As part of their education, nurses require information on cultural beliefs so that they can provide appropriate care to grieving mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 42 publications
0
43
0
Order By: Relevance
“…Women have reported a powerful sense of overwhelming loss, not only of the baby as a physical presence, but of joy and celebration, of parenthood, and their sense of self. Grieving after such a loss may be long-lasting, with significant adjustment problems (Bennett et al, 2008;Cacciatore, 2007;Kelley & Trinidad, 2012;Radestad, 2001;Turton, Evans, & Hughes, 2009), but both Western and Asian parents have reported that their grief was not socially recognized, and that they struggled with the silence that surrounded the stillbirth (Downe et al, 2013;Hsu, Tseng, Banks, & Kuo, 2004;Kelley & Trinidad, 2012;Lang et al, 2011). Women dared not openly discuss their children's deaths (Arnold & Gemma, 2008;Cacciatore, 2007;Lang et al, 2011;McCreight, 2008).…”
Section: Grief and Recovery After Stillbirthmentioning
confidence: 94%
See 1 more Smart Citation
“…Women have reported a powerful sense of overwhelming loss, not only of the baby as a physical presence, but of joy and celebration, of parenthood, and their sense of self. Grieving after such a loss may be long-lasting, with significant adjustment problems (Bennett et al, 2008;Cacciatore, 2007;Kelley & Trinidad, 2012;Radestad, 2001;Turton, Evans, & Hughes, 2009), but both Western and Asian parents have reported that their grief was not socially recognized, and that they struggled with the silence that surrounded the stillbirth (Downe et al, 2013;Hsu, Tseng, Banks, & Kuo, 2004;Kelley & Trinidad, 2012;Lang et al, 2011). Women dared not openly discuss their children's deaths (Arnold & Gemma, 2008;Cacciatore, 2007;Lang et al, 2011;McCreight, 2008).…”
Section: Grief and Recovery After Stillbirthmentioning
confidence: 94%
“…Women dared not openly discuss their children's deaths (Arnold & Gemma, 2008;Cacciatore, 2007;Lang et al, 2011;McCreight, 2008). Women blamed themselves for the deaths of their unborn children (Arnold & Gemma, 2008;Downe et al, 2013;Hsu et al, 2004;McCreight, 2008). Some parents blamed each other for the loss, creating strain in their relationships (Arnold & Gemma, 2008;Cacciatore, DeFrain, Jones, & Jones, 2008;Shaefer, 2010;Turton et al, 2009).…”
Section: Grief and Recovery After Stillbirthmentioning
confidence: 94%
“…1 In some settings, the underlying stigma of stillbirths may lead to underreporting. 40 In other settings, birth attendants may overreport stillbirths to protect their reputation as good delivery attendants in the community 41,42 or to avoid investigation procedures required for neonatal deaths. 29 In addition to the lack of a validated algorithm for stillbirths, deaths due to some causes are often included as a subset of another condition due to a lack of cases.…”
Section: Identification Of Gold Standards and Validationmentioning
confidence: 99%
“…We did not restrict our criteria to any particular definition or operationalization of self-blame, guilt, or shame. Exploratory studies that did not expressly seek to understand selfblame, guilt, or shame yet reported them in their results were excluded because doing so would bias the review by not also including all exploratory studies that did not find evidence of self-blame, guilt, or shame (e.g., Adolfsson, Larsson, Wijma, & Bertero, 2004;Clyman, Green, Rowe, Mikkelsen, & Ataide, 1980;DeFrain, Martens, Stork, & Stork, 1990;DeFrain, Millspaugh, & Xie, 1996;Frost & Condon, 1996;Hsu, Tseng, Banks, & Kuo, 2004;Mandell, McAnulty, & Reece, 1980;Robinson, 2011;Samuelsson, Radestad, & Segesten, 2001;Smialek, 1978;Taub, 1996). 3.…”
mentioning
confidence: 99%